TARI BANTENGAN DI DUSUN RANDEGAN, DESA JATIREJO, KABUPATEN MOJOKERTO - Mohammad Choerul Anam; F. Hari Mulyatno (Institut Seni Indonesia Surakarta, 2019)
Bantengan Dance is a dance depicting bull animals at war. The name of the Bantengan is taken because it adjusts to the bull animal as the main character in the Bantengan presentation. Based on the explanation above, the issue is formulated Related to the following problems: 1. How is the development of Bantengan dance at Dususn Randegan, Jatirejo village, Mojokerto Regency?, 2. How to form a Bantengan dance in the hamlet of Randegan, Jatirejo village in Mojokerto Regency?. This writing uses Sri Rochana’s opinion Widyastutieningrum that the development is an effort to package and make renewal of better direction and give new breath to the existing arts. The target of research is the issues related to the problems formulated above. This writing uses qualitative research methods that focus on the peculiarities and specificity of the object. This writing data is gathered with library studies, field observations, interviews, documentation, data analysis techniques. Results showed that the development of the form of dance presentation Bantengan want to show the presentation becomes more interesting and still enthused by the supporting community. The development of the Bantengan dance form is influenced by internal factors and external factors. Internal factors are the creativity of artists and leaders. External factors are government, technological developments, people’s outreach, social conditions and other performing arts competition. Keywords: Bantengan dance, development.